Synthesis, Characterization and Assessment of Carbendazim Based Mannich Analogues of Selected Clinical Agents - Khan Muhammad, Ishtiaq Ahmad, Hira Gul, Tahira Qamash, Nadia Mubarik, Zahir Ullah Khan, Mir Sadiq Shah, Muhammad Zia Ul Haq, Muhammad Junaid Khan, Saleem Jan (International Journal of Modern Agriculture, 2021)
Benzimidazole and its derivatives especially Carbendazime (methyl 2 benzimidazole carbamate or MBC) represent an important pharmacophore having a wide variety of biological activities. This study aimed to explore the derivatives of a heterocyclic pharmacophore called Carbendazime. The present study includes the synthesis of N-mannich base derivatives of Carbendazime through a classical mannich reaction. Mannich reaction is a three components condensation reaction involving the condensation of a pharmacophore with an aldehyde to form an iminium ion, and then the resultant ion again condensed with a compound containing secondary amine. In this study, new mannich base derivatives of Carbendazime with secondary amine (Diclofenac, Aceclofenac, diphenhydramine and silver sulfadiazine) was synthesized via mannich reaction. Thin layer chromatography (TLC) and melting point (MP) determination techniques was used to ascertain the purity of the newly synthesized derivatives. For the structural elucidation of the newly synthesized compounds spectral techniques like FTIR, NMR, and mass spectroscopy etc was performed. Different anti-oxidant activities like DPPH, GST, GSH, SOD and Catalyze was performed for determining the pro oxidant potential of the synthesized derivatives. To study the toxicity Brine shrimp lethality assay and MTT assay was performed. Disc diffusion method was used for evaluating antifungal activity of the newly synthesized library. Among the synthesized compounds, compound DS and compound SS shows significant anti-oxidant potential via the above anti-oxidant assays. Furthermore the compounds do not show any significant toxicity against peritoneal macrophages through MTT assay. All the compounds exhibit potential anti-fungal activity. A library containing 4 derivatives of Carbendazime was synthesized showing increase pharmacological potential compared to the parent compounds, and are very interesting and potential candidates for future studies.